2020
DOI: 10.1111/apm.13070
|View full text |Cite
|
Sign up to set email alerts
|

VGLL4 with low YAP expression is associated with favorable prognosis in colorectal cancer

Abstract: The Hippo pathway is a tumor suppressive pathway regulating Yes-associated protein-TEA domain-containing sequence-specific transcription factor (YAP-TEAD) complex. VGLL (Vestigial-like) proteins are transcriptional cofactors competing with YAP for TEAD binding and interfering oncogenic activity of YAP-TEAD complex. We evaluated the expression of VGLL4, YAP, and TEAD4 and assessed their correlations with clinicopathologic factors and prognostic effects in 295 colorectal cancers. VGLL4 was positive in 164 (55.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…Immunohistochemical staining was carried out as previously described [17]. Briefly, 4‐μm thick sections were cut from each TMA and deparaffinized and hydrated in xylene and serially diluted ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunohistochemical staining was carried out as previously described [17]. Briefly, 4‐μm thick sections were cut from each TMA and deparaffinized and hydrated in xylene and serially diluted ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…The immunohistochemical staining for YAP and TEAD4 was evaluated as previously described [12, 17]. The nuclear YAP and TEAD4 immunolabelings of the tumor cells were scored by multiplying the staining intensity (0, none; 1+, weak; 2+, moderate; and 3+, strong) and the proportion of stained cells (0, none; 1, <25%; 2, 25–50%; 3, 50–75%; and 4, >75%), thus having a range from 0 to 12.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vestigial-like Family Member 4 (VGLL4) is an important transcription cofactor. Relevant studies have shown that it can be a tumor suppressor to in uence the occurrence and development of tumors by promoting apoptosis of tumor cells [4,14,20]. In normal cells, it can also promote apoptosis as an inhibitor of apoptosis protein (IAP)-interacting protein [3,16].…”
Section: Introductionmentioning
confidence: 99%